Identification of a lifespan extending mutation in the Schizosaccharomyces pombe cyclin gene clg1+ by direct selection of long-lived mutants. - Bo-Ruei Chen (Public Library of Science (PLoS), 2013)
Model organisms such as budding yeast, worms and flies have proven instrumental in the discovery of genetic determinants of aging, and the fission yeast Schizosaccharomyces pombe is a promising new system for these studies. We devised an approach to directly select for long-lived S. pombe mutants from a random DNA insertion library. Each insertion mutation bears a unique sequence tag called a bar code that allows one to determine the proportion of an individual mutant in a culture containing thousands of different mutants. Aging these mutants in culture allowed identification of a long-lived mutant bearing an insertion mutation in the cyclin gene clg1(+). Clg1p, like Pas1p, physically associates with the cyclin-dependent kinase Pef1p. We identified a third Pef1p cyclin, Psl1p, and found that only loss of Clg1p or Pef1p extended lifespan. Genetic and co-immunoprecipitation results indicate that Pef1p controls lifespan through the downstream protein kinase Cek1p. While Pef1p is conserved as Pho85p in Saccharomyces cerevisiae, and as cdk5 in humans, genome-wide searches for lifespan regulators in S. cerevisiae have never identified Pho85p. Thus, the S. pombe system can be used to identify novel, evolutionarily conserved lifespan extending mutations, and our results suggest a potential role for mammalian cdk5 as a lifespan regulator.